The lipid metabolism in thraustochytrids. (October 2019) - Morabito, Christian; Bournaud, Caroline; Maës, Cécile; Schuler, Martin; Aiese Cigliano, Riccardo; Dellero, Younès; Maréchal, Eric; Amato, Alberto; Rébeillé, Fabrice
Abstract: Thraustochytrids are unicellular heterotrophic marine protists of the Stramenopile group, often considered as non-photosynthetic microalgae. They have been isolated from a wide range of habitats including deep sea, but are mostly present in waters rich in sediments and organic materials. They are abundant in mangrove forests where they are major colonizers, feeding on decaying leaves and initiating the mangrove food web. Discovered 80 years ago, they have recently attracted considerable attention due to their biotechnological potential. This interest arises from their fast growth, their specific lipid metabolism and the improvement of the genetic tools and transformation techniques. These organisms are particularly rich in ω3-docosahexaenoic acid (DHA), an 'essential' fatty acid poorly encountered in land plants and animals but required for human health. To produce their DHA, thraustochytrids use a sophisticated system different from the classical fatty acid synthase system. They are also a potential source of squalene and carotenoids. Here we review our current knowledge about the life cycle, ecophysiology, and metabolism of these organisms, with a particular focus on lipid dynamics. We describe the different pathways involved in lipid and fatty acid syntheses, emphasizing their specificity, and we report on the recent efforts aimed to engineer their lipid metabolism.